Addressing the risk and management of cardiometabolic complications in prostate cancer patients on androgen deprivation therapy and androgen receptor axis-targeted therapy: consensus statements from the Hong Kong Urological Association and the Hong Kong Society of Uro-Oncology - Poon, Darren M. C.; Tan, Guang-Ming; Chan, Kuen; Chan, Marco T. Y.; Chan, Tim-Wai; Kan, Raymond W. M.; Lam, Martin H. C.; Leung, Clarence L. H.; Wong, Kenneth C. W.; Kam, Kevin K. H.; Ng, Chi-Fai; Chiu, Peter K. F. (Frontiers in Oncology, 2024)
Background: Androgen deprivation therapy (ADT) is the foundational treatment for metastatic prostate cancer (PCa). Androgen receptor (AR) axis-targeted therapies are a new standard of care for advanced PCa. Although these agents have significantly improved patient survival, the suppression of testosterone is associated with an increased risk of cardiometabolic syndrome. This highlights the urgency of multidisciplinary efforts to address the cardiometabolic risk of anticancer treatment in men with PCa.Methods: Two professional organizations invited five urologists, five clinical oncologists, and two cardiologists to form a consensus panel. They reviewed the relevant literature obtained by searching PubMed for the publication period from April 2013 to April 2023, to address three discussion areas: (i) baseline assessment and screening for risk factors in PCa patients before the initiation of ADT and AR axis-targeted therapies; (ii) follow-up and management of cardiometabolic complications; and (iii) selection of ADT agents among high-risk patients. The panel convened four meetings to discuss and draft consensus statements using a modified Delphi method. Each drafted statement was anonymously voted on by every panelist.The panel reached a consensus on 18 statements based on recent evidence and expert insights.These consensus statements serve as a practical recommendation for clinicians in Hong Kong, and possibly the Asia-Pacific region, in the management of cardiometabolic toxicities of ADT or AR axis-targeted therapies in men with PCa.